PENGARUH KOMPETENSI DAN KEPUASAN KERJA TERDAHAP KINERJA KARYAWAN PADA PT. MALEA ENERGY KABUPATAN TANA TORAJA - Teresya Daun; Astriwati Biringkanae; Dina Ramba (Smart Education, 2026)
The purpose of this study was to determine whether Competence and Job Satisfaction influence Employee Performance at PT. Malea Energy, Tana Toraja Regency. Data collection procedures included observation, questionnaires, and documentation. The quantitative method used in this study was Multiple Linear Regression, processed using SPSS. This study was conducted on PT. Malea Energy employees in Tana Toraja Regency, with a sample size of 60 respondents. The sampling technique used was purposive sampling. The results of the t-test for the Competence variable showed a calculated t-count > t-table with a value of 5,294 > 2.002, and for the Job Satisfaction variable, a calculated t-count > t-table with a value of 5,960 > 2.002. The conclusion of this study is that Competence and Job Satisfaction influence Employee Performance at PT. Malea Energy, Tana Toraja Regency.